Direct and indirect effects of mass layoffs: Evidence from geo-referenced data - Philipp Vom Berge; Achim Schmillen (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
Using a novel data set that contains precise geo-referenced information on the universe of German establishments, we analyse both the direct effects of mass layoffs and any indirect impacts on workers who are employed in the vicinity of an establishment being closed down. In line with the literature, we document economically significant impacts of mass layoffs on the employment and earnings prospects of directly displaced workers. In contrast, neither an individual-level difference-indifference approach nor an alternative establishment-level approach inspired by the spatial economics literature find evidence of additional adverse economic effects for workers or establishments indirectly exposed to mass layoffs. – – Mit Hilfe eines neuen Datensatzes, der Betriebe in Deutschland mit einer exakten Geokoordinate versieht, untersuchen wir sowohl die direkten Effekte von Massenentlassungen, als auch den indirekten Effekt auf Personen, die in der Nähe der schließenden Betriebe beschäftigt sind. Wir bestätigen frühere Ergebnisse, die ökonomisch signifikante Effekte von Massenentlassungen auf Beschäftigungs- und Entlohnungsperspektiven von direkt betroffenen Beschäftigten fanden. Im Gegensatz dazu finden wir weder in einem Differenz-in-Differenzen-Ansatz auf individueller Ebene noch einem alternativen durch die räumliche Ökonomie inspirierten Ansatz auf Betriebsebene zusätzliche adverse Effekte auf Beschäftigte oder Betriebe, die nur indirekt durch eine Massenentlassung betroffen sind.
Keywords: J64; J65; R12; 330; mass layoffs; local general equilibrium effects; geo-referenced data